The Hitler book : the secret dossier prepared for Stalin from the interrogations of Otto Guensche and Heinze Linge, Hitler's closest personal aides. - Eberle, Henrik (PublicAffairs, 2009)
"An astonishingly intimate portrait" of the Führer--commissioned by, written for, and read by Joseph Stalin, before it disappeared into Soviet archives. Until now. (The Times).